2018
DOI: 10.1016/j.brainres.2018.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine inflammation reduces postnatal neurogenesis in the hippocampal subgranular zone and leads to accumulation of hilar ectopic granule cells

Abstract: Prenatal inflammation is associated with poor neurobehavioral outcomes in exposed offspring. A common route of exposure for the fetus is intrauterine infection, which is often associated with preterm birth. Hippocampal development may be particularly vulnerable to an inflammatory insult during pregnancy as this region remains highly neurogenic both prenatally and postnatally. These studies sought to determine if intrauterine inflammation specifically altered hippocampal neurogenesis and migration of newly prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 103 publications
(132 reference statements)
3
19
1
Order By: Relevance
“…Using a model of intrauterine inflammation that is similar to human pregnancies complicated by acute chorioamnionitis ( Elovitz and Mrinalini, 2005 ; Elovitz et al, 2011 ; Hester et al, 2018 ; Brown et al, 2019 ), we demonstrated that intrauterine LPS injection alters the placenta metabolome and is associated with marked changes in expression of genes involved in key pathways including vascular function and reactivity, mitochondria function and nutrient sensing, glucose and lipid metabolism, and ceramide and sphingosine-1-phosphate signaling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a model of intrauterine inflammation that is similar to human pregnancies complicated by acute chorioamnionitis ( Elovitz and Mrinalini, 2005 ; Elovitz et al, 2011 ; Hester et al, 2018 ; Brown et al, 2019 ), we demonstrated that intrauterine LPS injection alters the placenta metabolome and is associated with marked changes in expression of genes involved in key pathways including vascular function and reactivity, mitochondria function and nutrient sensing, glucose and lipid metabolism, and ceramide and sphingosine-1-phosphate signaling.…”
Section: Discussionmentioning
confidence: 99%
“…The University of Pennsylvania Institutional Animal Care and Use Committee approved all experiments in this study. Details of the intrauterine inflammation model have been previously published ( Elovitz and Mrinalini, 2005 ; Elovitz et al, 2011 ; Hester et al, 2018 ; Brown et al, 2019 ). CD-1 out-bred, timed pregnant mice were purchased from Charles River Laboratories (Wilmington, MA).…”
Section: Methodsmentioning
confidence: 99%
“…Such responses could stop at damage to the placenta or cross into the amniotic fluid (e.g. cytokines) or the fetus to cause damage to internal organs, including the brain [104,105] possibly leading to the processes that force medically indicated PTB or increasing morbidity in prematurely born infants. This later issue and the fetal defense against this is beyond the scope of this review and an extensive literature is elsewhere (e.g.…”
Section: The Immune-anatomy Of Maternal T Cells Pregnancy and Labormentioning
confidence: 99%
“…Importantly, various pathogens and the inflammatory response that follows the infection, affect the fetal development (especially the developing fetal lung and brain), and may also impact the long-term health of the infant (70). IAI can affect different neurological developmental processes, inducing neuroinflammation, cerebral palsy, and periventricular white matter injury in the fetus, and even neuropsychiatric diseases have been linked to IAI (71)(72)(73)(74)(75)(76). Chronically damaged lungs in the form of bronchopulmonary dysplasia are also highly associated with IAI (77)(78)(79).…”
Section: Intra-amniotic Infection and Inflammationmentioning
confidence: 99%